(untitled) (Economic and Political Thought, 2014)
The aim of this text is to present Polish non-academic economic theories inspired by the concept of ‘social credit’ developed by Clifford Hugh Douglas. The focus of the current analysis is not only the theories as such, but also social conditions for their emergence, construction and functioning. Most of the ideas for reconstructing the financial and social system come from a community close to the foundation called We are Change. The essential element of the presented concepts is the idea of basic income, also called a ‘social/national dividend’.